The Welsh Single-Use Carrier Bag Charge and behavioural spillover. (September 2016) - Thomas, Gregory Owen; Poortinga, Wouter; Sautkina, Elena
Abstract: A Single-Use Carrier Bag Charge (SUCBC) requires bags to be sold for a small fee, instead of free of charge. SUCBCs may produce 'spillover' effects, where other pro-environmental attitudes and behaviours could increase or decrease. We investigate the 2011 Welsh SUCBC, and whether spillover occurs in other behaviours and attitudes. Using the Understanding Society Survey ( n = 17, 636), results show that use of own shopping bags increased in Wales, compared to England and Scotland. Increased use of own bags was linked to increases in six other sustainable behaviours, although changes were significantly smaller in Wales for three of these behaviours. Increased own bag use was linked to stronger environmental views, but effects were weaker in Wales for two out of three measures. We conclude that the Welsh SUCBC effectively encouraged bag re-use, but with minimal changes in other environmental attitudes and behaviours, due to the external motivation to change behaviour. Highlights: Analysis of dataset representative of the UK population (n = 17, 636). Sustainable behaviours and views measured pre/post Carrier Bag Charge in Wales. Carrier Bag Charge linked to increased frequency of bringing own shopping bags. Greater use of own bags linked to general increase in six other sustainable actions. Wales sample show weaker spillover links, likely due to external motivation.